Arm’s Length Financing and Innovation: Evidence from Publicly Traded Firms - Atanassov, Julian (Management Science, 2016)
Using a large panel of U.S. companies, I document that firms that rely more on arm’s length financing, such as public debt and equity, innovate more and have higher-quality innovations than firms that use other sources, such as relationship-based bank financing. I hypothesize that one possible reason for this finding is the greater flexibility and tolerance to experimentation associated with arm’s length financing. I find support for this hypothesis by showing that firms with more arm’s length financing have greater volatility of innovative output, and are more likely to innovate in new technological areas. Furthermore, focusing only on bank financing, I demonstrate that firms have more novel innovations if they borrow from multiple banks, use predominantly credit lines, and have less intense covenants. I address potential endogeneity concerns by using instrumental variable analysis, and by showing that innovation increases significantly after new public debt offerings and seasoned equity offerings, but does not change after new bank loans. This paper was accepted by Gustavo Manso, finance.